THE EFFECT OF BUDGET TARGETS CLARITY, INFORMATION ASYMMETRICITY, AND SELF ESTEEM ON BUDGETARY SLACK WITH ORGANIZATIONAL COMMITMENT AS A MODERATING VARIABLE: A LITERATURE REVIEW STUDY - Zahrani, Olivia Putri; Mukhtaruddin, Mukhtaruddin (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
This study aims to provide a summary of budgetary slack. Through the systematic literature review (SLR) method, this study focuses on reviewing how budget target clarity, information asymmetry, and self-esteem affect budgetary slack with organizational commitment moderation. This literature study focuses on 49 journal articles, which are dominated by research articles indexed by Sinta 2 to Sinta 5 for 10 years in the period 2016-2025. The findings show that agency theory is the most commonly used theory in research on budget target clarity, information asymmetry, self-esteem, organizational commitment and budgetary slack. Based on the literature study conducted by the researcher, previous research on the relationship between budget target clarity, information asymmetry, self-esteem and budgetary slack with organizational commitment moderation still has inconsistent results. This is caused by various factors such as the research period, sample characteristics, data collection methods, measurements used, and the place and type of sector studied.